If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 9 = 2y + -4 Reorder the terms: 9 + 3x = 2y + -4 Reorder the terms: 9 + 3x = -4 + 2y Solving 9 + 3x = -4 + 2y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + 3x = -4 + -9 + 2y Combine like terms: 9 + -9 = 0 0 + 3x = -4 + -9 + 2y 3x = -4 + -9 + 2y Combine like terms: -4 + -9 = -13 3x = -13 + 2y Divide each side by '3'. x = -4.333333333 + 0.6666666667y Simplifying x = -4.333333333 + 0.6666666667y
| 6m^2+15m+3=0 | | -2x+5=10+4x | | 2x+4=-x-20 | | 22=2y | | 0=x^2+26x+232 | | x+1+2x+2+3x+3+4x=56 | | 2x+7=-x-1 | | 11x-79=47+5x | | 5x-3+2x=2x+2 | | 8=2*b^2 | | (x*x)-5=23 | | 8=2xb^2 | | -4+3x-1=4x+1 | | sin(19x)+sin(7x)=0 | | 64m=cm | | -16n+19=-15n-13 | | c=36(n+16) | | (5x+6y)(5x-6y)=0 | | 8=2(x-2) | | 45=9f | | 5x+6x=-11 | | X^3-3x^2-9x+3=0 | | (4x-5)(3-2x)=12-9(2x-5) | | 9+2+4=183652 | | 3(5x+6x)=108 | | 4x-72=-36 | | 4(x-14)=160 | | 4t+20-15= | | y=-4x^2+2x-3 | | 0=x^2+20x+208 | | 0=x^2+20+208 | | 40=2x+5+2x-3 |